(3GddSGfjGJ GdYQHjI (B:s (3eLdI YdejI aUdjI eMceI JUOQ Yf eQcR Gdedc YHO Gddg Hf YHO GdYRjR GdOhdj dNOeI GddZI GdYQHjI (B/s - (3eQcR Gdedc YHO Gddg Hf YHO GdYRjR GdOhdj dNOeI GddZI GdYQHjIs; (3GdYUjdj, YHO GdYRjR Hf EHQGgje,s 1375 (3gLQj(B-s ((3GdQjGV (B:s (3eQcR Gdedc YHO Gddg Hf YHO GdYRjR GdOhdj dNOeI GddZI GdYQHjIs, 2015)
(3JJfGhd GdeLdI GdOQGSI GdYdejI GdMOjKI ddZI GdYQHjI ef efXhQ Ydej dSGfj MOjK, hJgJe HGdOQGSGJ GdYdejI GdQUjfI GdJj JJfGhd GddZI GdYQHjI ef YOI RhGjG dSGfjI eYGUQI hef RhGjG dZhjI eNJdaI, MjK JYfi HOQGSGJ hHMhK Ydhe GddZI GdebGQfI hGdJbGHdjI hGdJWHjbjI, hGdOQGSGJ hGdHMhK GdJj JhXa JWHjbGJ GdeOGQS GddZhjI GdMOjKI GdGLJeGYjI hGdHfjhjI hGdJhdjOjI GdJMhjdjI, hGdOQGSGJ GdJOGhdjI, hdSGfjGJ GdfU hJMdjd GdNWGH(B.s
(3BNQ YOO Je GdQLhY Edjg(B: (3Y(B5 ((3QeVGf (B1438(3g` jhfjh (B2017(3e(B)s
(3GdhUa eCNhP ef (B: (3GdYOO (B2 ((3jfGjQ (B2015)s
(3BNQ YOO Je JOGhdg (B: (3GdYOO (B9 ((3jhdjh (B2019)s
Keywords: (3GddZI GdYQHjIs -- (3OhQjGJs; (3GdCOH GdYQHjs -- (3OhQjGJs